IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH GUESSING GAMES AT GRADE X OF SMA NEGERI 1 HUTABARGOT - Purba, Happy Sri Rezeki; Elisa (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2024)
The aim of the research was to know whether students’ speaking skills can be improve by using guessing games at Grade X of SMA Negeri 1 Hutabargot. To obtain the research data, researcher used classroom action research (CAR) and as sample was Grade X MIA consisted of 22 students. As the technique in collecting data, the researcher used speaking test, interview and also questionnaire. Based on the result analysis, it can be seen that the mean score of the students’ speaking ability in pre-test was 43,63%. While the mean score of the post-test in cycle 1 was 54,81%. The mean score of the post-test in cycle 2 was 77.81%. From the comparison between the mean scores of the pre-test and post-test, it can be identified that the implementation of a guessing game could improve students’ speaking ability Keywords: Improving, Guessing Game, Speaking